The role of Interleukin-32 in autoimmunity - Albuquerque Rafael; Komsi Elina; Starskaia Inna; Ullah Ubaid; Lahesmaa Riitta (WILEY, 2022)
Interleukin-32 (IL-32) is a pro-inflammatory cytokine that induces other cytokines involved in inflammation, including tumour necrosis factor (TNF)-alpha, IL-6 and IL-1 beta. Recent evidence suggests that IL-32 has a crucial role in host defence against pathogens, as well as in the pathogenesis of chronic inflammation. Abnormal IL-32 expression has been linked to several autoimmune diseases, such as rheumatoid arthritis and inflammatory bowel diseases, and a recent study suggested the importance of IL-32 in the pathogenesis of type 1 diabetes. However, despite accumulating evidence, many molecular characteristics of this cytokine, including the secretory route and the receptor for IL-32, remain largely unknown. In addition, the IL-32 gene is found in higher mammals but not in rodents. In this review, we outline the current knowledge of IL-32 biological functions, properties, and its role in autoimmune diseases. We particularly highlight the role of IL-32 in rheumatoid arthritis and type 1 diabetes.